Seismogenic structure beneath the northern Longitudinal Valley revealed by the 2018–2021 Hualien earthquake sequences and 3-D velocity model - Hsin-Hua Huang; Yu Wang (Terrestrial, Atmospheric and Oceanic Sciences, 2022)
Key Points 1. Earthquake relocations and the 3D velocity model suggest a westward dipping structural boundary exists beneath the coastal range. 2. The 2021 earthquake cluster is likely sourced from this structural boundary 3. The northward extension of this structural boundary is likely connecting to the main rupture fault of the 2018 Hualien earthquake.